Observation of mesospheric gravity waves at Comandante Ferraz Antarctica Station (62° S) - Bageston, J. V.; Wrasse, C. M.; Gobbi, D.; Takahashi, H.; Souza, P. B. (Annales Geophysicae, 2009)
An airglow all-sky imager was operated at Comandante Ferraz Antarctica Station (62.1° S, 58.4° W), between April and October of 2007. Mesospheric gravity waves were observed using the OH airglow layer during 43 nights with good weather conditions. The waves presented horizontal wavelengths between 10 and 60 km and observed periods mainly distributed between 5 and 20 min. The observed phase speeds range between 5 m/s and 115 m/s; the majority of the wave velocities were between 10 and 60 m/s. The waves showed a preferential propagation direction towards the southwest in winter (May to July), while during spring (August to October) there was an anisotropy with a preferential propagation direction towards the northwest. Unusual mesospheric fronts were also observed. The most probable wave source could be associated to orographic forcing, cold fronts or strong cyclonic activity in the Antarctica Peninsula.